CHANGES IN NUCLEIC ACIDS AND PROTEIN CONTENT OF TILAPIA MOSSAMBICA EXPOSED TO DICHLORVOS (DDVP) - Rath, S; Misra, B N (Indian Journal of Fisheries, 2011)
Changes in nuckic acids and protein content in liver, muscle and brain ofa freshwater fish Tilapia mossambica -Peters, exposed to a sub-lethal concentrationof 0.5 mg. 1-^ of the i.nsectic'de, Dichlorvos (DDViP) for a period of 21days vfere studied. The exposed fish showed a lower brain and liver somatic•indices suggesting loss of oells. Post-exposure studies revealed a significant declinein DN.\, RN.\ and prote'n contents of liver, muscle and brain. The liverexhibited a greater loss in DNA, RNA and protein contents than those of muscleand brain in the exposed fish. Inhibitory effect of the insecticide on nucleic acids .and protein content was martedly elevated by the increase in the exposure period